2021
DOI: 10.31849/elsya.v3i2.5794
|View full text |Cite
|
Sign up to set email alerts
|

The Difficulties in Implementing Scientific Approach Based on 2013 Curriculum: A Case Study on One English Teacher

Abstract: This case study investigated the difficulties faced by an English teacher in implementing the scientific approach at one selected school in the district of Agam in West Sumatera, Indonesia. This qualitative research used semi-structured interview questions and an observation checklist as the instruments, with an English teacher as the data source. This study showed that the selected secondary English teacher in MTsN 3 Agam encountered eight significant difficulties in dealing with the implementation of stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Other findings also report that teachers who do not have digital literacy skills will have difficulty developing HOTS-based assessments (Widana, 2020). Similar research also found that teachers faced difficulties when implementing a scientific approach, especially promoting students to ask questions and analyze (Madina & Kardena, 2021). The scientific approach supported by HOTS-based classroom assessment from the teacher is believed to be able to improve students' abilities and achievements.…”
mentioning
confidence: 73%
“…Other findings also report that teachers who do not have digital literacy skills will have difficulty developing HOTS-based assessments (Widana, 2020). Similar research also found that teachers faced difficulties when implementing a scientific approach, especially promoting students to ask questions and analyze (Madina & Kardena, 2021). The scientific approach supported by HOTS-based classroom assessment from the teacher is believed to be able to improve students' abilities and achievements.…”
mentioning
confidence: 73%